Gambaran Motivasi Siswa Mtsn 5 Muarasipongi Kabupaten Mandailing Natal Dalam Mengikuti Kegiatan Ekstrakurikuler - Zulhanuddin Zulhanuddin; Arif Fadli Muchlis; Donal Syafrianto; Liza Liza (JURNAL STAMINA, 2022)
The problem in the study started from the implementation of extracurricular activities that did not go well, where students often did not attend training. It is suspected that one of the factors causing this problem is student motivation. This study aims to determine the motivation of students at MTsN 5 Muarasipongi, Mandailing Natal Regency in participating in extracurricular activities. This type of research is descriptive. The population in this study were all students who took part in extracurricular activities totaling 40 people. The sampling technique used was total sampling. Thus the sample in this study amounted to 40 students. The instrument used to collect data is a questionnaire or questionnaire using a Likert scale, where previously the validity and reliability tests were carried out. The data were analyzed using the frequency distribution formula in the form of percentages. The results of the study were obtained as follows: The level of student motivation in participating in extracurricular activities at MTsN 5 Muarasipongi was 59.78%, in the medium classification. This means that students in participating in extracurricular activities at MTsN 5 Muarasipongi have moderate motivation and ned to be improved, both from intrinsic motivation and from extrinsic motivation